2017
DOI: 10.2527/jas.2016.1071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a major quantitative trait locus for porcine reproductive and respiratory syndrome (PRRS) resistance on response to coinfection with PRRS virus and porcine circovirus type 2b (PCV2b) in commercial pigs, with or without prior vaccination for PRRS1

Abstract: A major QTL for host response to porcine reproductive and respiratory syndrome (PRRS) virus (PRRSV) infection was identified in a previous study. Single nucleotide polymorphism WUR10000125 (WUR), which is in complete linkage disequilibrium with the putative causative mutation, can be used as a tag SNP for the QTL. However, the effect of WUR following PRRS vaccination and/or coinfection with other pathogens is not known. Therefore, objectives of this study were to estimate the effect of WUR on host response fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…Results from Dunkelberger et al [ 7 ] showed that WUR had a significant effect on vaccination VL as well as PRRS VL and PCV2b VL of Vx pigs, but not PCV2b VL of Non-Vx pigs. Results also showed that, numerically, the effect of WUR on PRRS VL was greater following primary versus secondary PRRSV exposure, which is consistent with the biological role of GBP5 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results from Dunkelberger et al [ 7 ] showed that WUR had a significant effect on vaccination VL as well as PRRS VL and PCV2b VL of Vx pigs, but not PCV2b VL of Non-Vx pigs. Results also showed that, numerically, the effect of WUR on PRRS VL was greater following primary versus secondary PRRSV exposure, which is consistent with the biological role of GBP5 .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the animals used for this study is in Dunkelberger et al [ 7 ]. Briefly, commercial Large White x Landrace crossbred barrows from two experimental co-infection trials (trial 1 n = 199; trial 2 n = 197) were used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations